Nanocomposite Materials for Biomedical and Energy Storage Applications - Sharma, Ashutosh (IntechOpen, 2022)
Nanocomposite Materials for Biomedical and Energy Storage Applications presents an overview of various types of advanced nanostructured and nanocomposite materials. It discusses current research trends, problems, and applications of these nanomaterials in various biomedical, energy conversion, and storage applications. The book also gives a brief overview of advances in conducting polymers and their applications in electronic devices. Chapters address such topics as nanocomposite materials and their fabrication, nanocomposite materials for energy conversion and energy storage devices, advanced nanocomposite materials in biomedicine and health care, nanocomposites in organic light-emitting diodes and display devices, and much more.